2022
DOI: 10.21037/atm-22-5225
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 overexpression mediated by the inhibition of transcription factor SOX9 protects against hypoxia-/reoxygenation-induced injury in hippocampal neurons by activating Nrf2/HO-1 signaling

Abstract: Background: Cerebral ischemia/reperfusion (CI/R) injury is a destructive cerebrovascular disease associated with long-term disability and high mortality rates. TGR5 has been discovered in multiple human and animal tissues and to modulate a variety of physiological processes. The current study sought to reveal the function of TGR5 in CI/R injury and uncover the latent regulatory mechanism.Methods: A hypoxia/reoxygenation (H/R) model was established in mouse hippocampal HT22 cells.The TGR5 expression in the H/R-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…36 Another study showed that TGR5 overexpression in hippocampal neurons can protect against hypoxia-/reoxygenation-induced injury by activating Nrf2 signaling. 37 Here, we also found that after TCA infusion, the TGR5s located on the surface of the neurons in the PVN were activated as their expression increased (Fig. 6).…”
Section: Paper Food and Functionsupporting
confidence: 65%
“…36 Another study showed that TGR5 overexpression in hippocampal neurons can protect against hypoxia-/reoxygenation-induced injury by activating Nrf2 signaling. 37 Here, we also found that after TCA infusion, the TGR5s located on the surface of the neurons in the PVN were activated as their expression increased (Fig. 6).…”
Section: Paper Food and Functionsupporting
confidence: 65%